The Impact of New Entrepreneurial Spirit on Cultivating Entrepreneurial Values and Entrepreneurial Ability of College Students - Li, Ping; Chen, Xiaozhou (Frontiers in Psychology, 2022)
The objectives are to deeply study the impact of new entrepreneurial spirit on the cultivation of entrepreneurial values and entrepreneurial ability of college students. Firstly, the influencing factors of college students’ entrepreneurial values are analyzed based on new media, entrepreneurial spirit, entrepreneurial values and other related theories. Secondly, the corresponding questionnaire is designed and elaborated on the four aspects of college students’ entrepreneurial values, entrepreneurial competence, entrepreneurial risk as well as entrepreneurial ethics. Finally, the data results of the questionnaire are studied. The results show that in entrepreneurial values of college students, they believe that entrepreneurship is the most important to personal development, with an overall average of 3.86. In the point of view of entrepreneurial competence, they think that independent learning ability plays a significant role in entrepreneurship, with an average of 3.91. In the view of entrepreneurial ethics, they consider that the law is the most crucial during the entrepreneurial, with an average value of 4.35. It means that college students still have certain legal knowledge. After analyzing the results of the questionnaire on entrepreneurial factors, it is found that college students lack social experience and have a low ability to take risks. Meanwhile, entertainment is the first choice for college students on new media platforms, and the time of viewing is more than 5 hours per day. Therefore, the influence of new entrepreneurial spirit is researched on the cultivation of entrepreneurial values and entrepreneurial ability of college students, which provides a new theoretical basis and optimization direction for entrepreneurial education in universities in the future.